A STUDY ON IMPACT OF ADVERTISING ON CONSUMERS BUYING BEHAVIOR WITH REFERENCE TO SELECTED FMCG - Devi, Mrs S.P Shobha; Vemula, Dr. Rajesh; Poojitha, Dr. Sabbineni (The journal of contemporary issues in business and government, 2022)
Understanding of the consumers buying behavior and examining procedures of decision making necessitates the need to identify the awareness towards advertising of the FMCG products that offers relevant product information to the consumer. This paper aims to explore the role of advertisement on attitudes towards buying behavior. Questionnaire has prepared to evaluate the impact of advertisement. Here, the researchers have used convenience sampling method for distributing the questionnaire in order to study the impact of advertising on consumers buying behaviour with special reference to FMCG products. The study was carried out involving a survey on 180 sample size and the consumer are chosen the age limit of 18-45 years in Bangalore City. Five brands have been taken into consideration as FMCG’s brand Parle Agro, ITC, Dabur India, HUL and Britannia. According to the analyzed data, advertisement variables show a positive impact on consumer buying behavior in Bangalore city. According to the regression analysis Brand of products shows more impact of the consumer buying behavior than a label and environmental advertisement. These results of this research exposed that advertisement attracts towards the preference and choices to influence the consumer buying behavior.